Proton-Coupled Electron Transfer in the Reaction of 3, 4-Dihydroxyphenylpyruvic Acid with Reactive Species in Various Media. (28th January 2015) - Fifen, J. J.; Dhaouadi, Z.; Nsangou, M.; Holtomo, O.; Jaidane, N.
Abstract : The distinction of concerted proton-coupled electron transfer (CPCET) from sequential one as well as proton transfer-electron transfer (PT-ET) from electron transfer-proton transfer (ET-PT) in the O–H bond cleavage reactions in various media has always been a difficult task. In this work, the activation barrier of the CPCET mechanism, its rate constants, and reaction free energies related to ET-PT and PT-ET involving coreactive species were presented as good parameters to attempt the problem. DFT calculations were carried out studying the described pathways subsequent to the scavenging ofOH andOBr - by the 3, 4-DHPPA in various media. The solvation was described in a hybrid manner using IEF-PCM model conjointly with a model that takes into account some solute-solvent interactions. As a result, we found that the scavenging of hydroxyl radical by 3, 4-DHPPA is thermodynamically governed by a one-step hydrogen atom transfer (CPCET) from the acid to the radical in all media. In kinetic viewpoint, CPCET still dominates in the vacuum and in nonpolar solvents, but in polar solvents it could compete strongly with the ET-PT mechanism so that the latter could slightly dominate.